Aryl Sulfotransferase from Haliangium ochraceum: A Versatile Tool for the Sulfation of Small Molecules. Issue 4 (26th March 2014) - Ayuso‐Fernández, Iván; Galmés, Miquel A.; Bastida, Agatha; García‐Junceda, Eduardo
Abstract Sulfation is an important molecular modification that regulates essential cellular processes and is also implicated in numerous pathological processes. The enzymes responsible for this reaction in living organisms are sulfotransferases. The gene Hoch_5094 from Haliangium ochraceum is annotated as a putative sulfotransferase. The arylsulfotransferase codified by this gene (HocAST) was expressed heterologously in E. coli and showed aryl sulfotransferase activity. Circular dichroism analysis of HocAST showed a main α/β secondary structure that agrees with the overall structure of other cytosolic sulfotransferases. Interestingly, HocAST was able to use both p‐nitrophenyl sulfate and 3′‐phosphoadenosine‐5′‐phosphosulfate (PAPS) as sulfuryl donors contrary to that of aryl sulfate sulfotransferase, which cannot use PAPS as a donor. Regarding the specificity towards the acceptor, HocAST has shown quite a wide scope and was able to accept several mono‐ and dihydroxylated phenols and other phosphorylated compounds as substrates.